2016
DOI: 10.1161/strokeaha.115.010477
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Feasibility, and Efficacy of Vagus Nerve Stimulation Paired With Upper-Limb Rehabilitation After Ischemic Stroke

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
267
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(275 citation statements)
references
References 30 publications
7
267
0
1
Order By: Relevance
“…In this open-label study, patients who received VNS paired with rehabilitation demonstrated 3-fold greater improvement in Upper Extremity Fugl-Meyer score compared to patients who received rehabilitation without VNS (Dawson et al, 2015), providing an initial demonstration that VNS may improve post-stroke recovery. The present preclinical study provides additional proof-of-concept support and suggests that VNS therapy may provide benefits for elderly patients as it translated to the broader clinical population of stroke patients.…”
Section: Discussionmentioning
confidence: 92%
“…In this open-label study, patients who received VNS paired with rehabilitation demonstrated 3-fold greater improvement in Upper Extremity Fugl-Meyer score compared to patients who received rehabilitation without VNS (Dawson et al, 2015), providing an initial demonstration that VNS may improve post-stroke recovery. The present preclinical study provides additional proof-of-concept support and suggests that VNS therapy may provide benefits for elderly patients as it translated to the broader clinical population of stroke patients.…”
Section: Discussionmentioning
confidence: 92%
“…Based on these studies, Dawson et al [67,68] evaluated VNS paired with physical rehabilitation in a pilot study in stroke patients. Although designed as a safety study, VNS was paired with several typical rehabilitative tasks over the course of 6 weeks of physical rehabilitation.…”
Section: Preclinical and Clinical Studies For Ischemic Strokementioning
confidence: 99%
“…35 A recent RCT of vagal nerve stimulation to augment upper-limb rehabilitation following stroke was shown to be safe and feasible. 40 Further prospective studies are necessary to evaluate the efficacy of this modality.…”
Section: Cerebellar Stimulationmentioning
confidence: 99%